(untitled) (Third Sector Social Economic Review, 2021)
Within the framework of the theoretical infrastructure of organizational ecology, the present study aims to understand the effect of the macro-level economic phenomena observed within a specific time interval on the founding and disbanding of cooperative organizations in agriculture, forestry, and fisheries sector of Turkey. Besides, the effects of the Covid-19 pandemic were also taken under focus. Focusing on the time period between January-2010 and December-2020; the number of founding and disbanding of cooperative companies operating in the agriculture, forestry, and fisheries sector, the producer price index of agricultural products, weighted average of commercial loan interest, and US Dollar-Turkish Lira exchange rate were used as data. Additionally, the period of the Covid-19 pandemic between March-2020 and December-2020 was included in the analysis as a dummy variable. ARDL bounds test was used for analyzing the data. The findings indicate the differentiated effects of the producer price index of agricultural products, the weighted average of commercial loan interest, and US Dollar-Turkish Lira exchange rate, and the Covid-19 pandemic on population of cooperative organizations which operate in the agriculture, forestry, and fisheries sector.